First report of field remediation of contaminated tailings from the collapsed Fundão dam in Brazil - Scotti, Maria Rita; Avila, Stephania S.; Mendes, Leonardo; Lacerda, Tomas J.; Silva, Samuel Lourenço L.; Antão, Arthur C.; Gomes, Alessandra R.F.; Medeiros, Mirelli B.; Alvarenga, Stael; Santos, Carlos Henrique B. [UNESP]; Rigobelo, Everlon C. [UNESP] (Avestia Publishing, 2019)
The failure of the Fundão dam in Brazil spilled contaminated sediments to the Doce river basin with high levels of pH,ether-amine and sodium. In the present study, it was established a riparian forest over contaminated sediment using two main remediation strategies: phytoremediation with native species to the Atlantic Forest, previously selected for tolerance to the sediment toxicity, and physico-chemical remediation by management of the sediment with incorporation of OM. In the experimental site (ES), 12 native species were cultivated under two treatments: T1- management of the sediments with incorporation of OM and T2- nonmanaged sediment + superficial deposition of OM. The results were compared with a degraded site (DS) affected by the contaminated sediments and a preserved site (PS) composed of a fragment of preserved Atlantic Forest. After 6 month of transplanting, plants from T1 showed a better height growth performance (up to 3m) and survival index in relation to T2, as well as a significant decline of ether- amine and sodium contents. Besides the improvement of soil fertility, the amendment with OM promoted a pH reduction, favoring ether-amine destabilization, sodium sequestration and improvement of soil microbial populations. Soil nitrification was improved as revealed by the significant increase of nitrate which seems to have favoured the rampant growth of tolerant plant species after 6 months of planting. Therefore, it is recommended the incorporation of OM to the sediment and phytoremediation with selected tolerant species to remediate sodium and ether-amine toxicity.
Keywords: Dam tailings; Ether-amine; PH; Phytoremediation; Reclamation; Sodium